Some characteristics of the river-grown and reared smolts of the Latvian salmon - Mitans, A.R. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1968)
The optimum terms of release of the smolts reared in hatcheries and their main features were determined. The chief attention was paid to the definition of some morphological indices, the determination of which does not require specific apparatus and can be accessible for every fish-breeder. The material on the ecological and biological features of smolts was sampled mainly in the Salaca River (Latvia) from 1964 to 1966. During this period 2110 smolts of this river were measured and aged. For the composition of the morphological characteristics the results of measurements of 283 smolts were used. Of them 240 belonged to salmon (Salmo salar) and 37 - to sea trout (Salmo trutta). The advice on the rearing and the release of smolts was presented for the fish hatcheries. Published Not Known